Circadian Rhythms Coordinated With Gut Microbiota Partially Account for Individual Differences in Hepatitis B-Related Cirrhosis - Wang, Tongyao; Rong, Xingyu; Zhao, Chao (Frontiers in Cellular and Infection Microbiology, 2022)
Cirrhosis is the end stage of various liver diseases, including viral hepatitis, alcoholic liver disease (ALD), non-alcoholic fatty liver disease (NAFLD), metabolic diseases, and other chronic liver diseases. In China, hepatitis B accounts for around 60% of cases of cirrhosis. So far, clinical and laboratory indexes for the early diagnosis of cirrhosis are far from satisfactory. Nevertheless, there haven’t been specific drugs for cirrhosis. Thus, it is quite necessary to uncover more specific factors which play their roles in cirrhosis and figure out the possible therapeutic targets. Among emerging factors taking part in the initiation and progression of cirrhosis, gut microbiota might be a pivot of numerous systemic factors like metabolism and immune. What’s more, the gut-liver axis makes gut microbiota a more direct and influential element. The researches on mechanisms involving gut microbiota have been stepping from systemic stage to molecular stage. This leads to a more promising prospect of developing new drugs intervening in pathways related to gut microbiota. Besides new targets and molecules, specifying the medication regimen also helps enhance the effects of existing therapies. Time-based medication regimen has been proofed to be helpful in hormonotherapy, especially in the use of glucocorticoid. Thus, circadian rhythms, though haven’t been strongly linked to hepatitis B and its complications, are still pivotal to the synchronicity of every part and system of the body. Being discordant with intrinsic diurnal rhythms can lead to a series of health problems. Gut microbiota as a potential effective factor of circadian rhythms has also received increasing attentions. Here, our work, restricting cirrhosis to the post-hepatitis B one, is aimed to summarize how circadian rhythms and hepatitis B-related cirrhosis can intersect via gut microbiota, and to throw new insights on the development of new and time-based therapies for hepatitis B-related cirrhosis and other cirrhosis.